The implementation of a public health alcohol policy in Ireland. (6th March 2023) - Barry, J.; Lyne, J.
Abstract: In 2012, the Irish Department of Health published a strategy in relation to alcohol and flagged that a Public Health (Alcohol) Act would be pursued through the Houses of the Oireachtas. This Public Health (Alcohol) Act was intended to reduce alcohol consumption and the harms caused by the misuse of alcohol. The act includes various means for this purpose, including introducing statutory minimum prices on alcohol, restricting alcohol advertising, addition of warning labels to alcohol products, and reducing the visibility of alcohol products in retail outlets. This perspective piece aims to provide an account of how this public health alcohol policy has been implemented in Ireland. The strategy relied in a major way on the World Health Organisation framework for alcohol policy. It took 3 years from the launch of that strategy to get the Public Health (Alcohol) Bill published, in December 2015. It took almost another 3 years to get the Public Health (Alcohol) Act passed by the Houses of the Oireachtas, in October 2018. The Act was signed into law by the President of Ireland in November 2018, and it's implementation has commenced in the last few years. This perspective piece highlights the complexities and challenges of implementing legislation related to public health policy, but also demonstrates that real action can occur with advocacy from public health clinicians and key stakeholders.